HybPhyloMaker: Target Enrichment Data Analysis From Raw Reads to Species Trees. (2nd January 2018) - Fér, Tomáš; Schmickl, Roswitha E
Summary: Hybridization-based target enrichment in combination with genome skimming (Hyb-Seq) is becoming a standard method of phylogenomics. We developed HybPhyloMaker, a bioinformatics pipeline that performs target enrichment data analysis from raw reads to supermatrix-, supertree-, and multispecies coalescent-based species tree reconstruction. HybPhyloMaker is written in BASH and integrates common bioinformatics tools. It can be launched both locally and on a high-performance computer cluster. Compared with existing target enrichment data analysis pipelines, HybPhyloMaker offers the following main advantages: implementation of all steps of data analysis from raw reads to species tree reconstruction, calculation and summary of alignment and gene tree properties that assist the user in the selection of "quality-filtered" genes, implementation of several species tree reconstruction methods, and analysis of the coding regions of organellar genomes. Availability: The HybPhyloMaker scripts, manual as well as a test data set, are available inhttps://github.com/tomas-fer/HybPhyloMaker/ . HybPhyloMaker is licensed under open-source license GPL v.3 allowing further modifications.